La réaction de la doctrine à la création judiciaire en droit pénal - Jodouin, André (Les Cahiers de droit, 1980)
This article is a survey of the attitudes of legal writers concerning judicial creation. A number of articles, studies and case comments in the areas of mens rea, duress and drunkenness are canvassed in order to determine their authors' views on the legitimacy of the rules established by courts in the above areas. Judicial creation often involves departures from traditional legal reasoning; the attitude of legal writers towards these departures is also studied. Finally, it is sought to establish the views of the doctrine on the characteristics and qualities which judicial creation should present. A number of points emerge from the study : attitudes towards judicial creation are generally favorable. The legitimacy of the creative role is most often taken for granted. As regards judicial reasoning, departures from stare decisis are generally seen as valid ; less unanimity is reached on departures from traditional rules of construction. There does not appear to be any perceptible difference between the attitudes of common law and civilian writers on judicial creation except on the point of rules of construction, where civilians seem somewhat more inclined to traditional views. In all cases, it was found difficult to determine the philosophical perspectives of the writers although these would normally be expected to have a strong bearing on the issue oj judicial creativity.